The Cleft Aesthetic Rating Scale for 18-Year-Old Unilateral Cleft Lip and Palate Patients: A Tool for Nasolabial Aesthetics Assessment. (August 2018) - Mulder, F.J.; Mosmuller, D.G.M.; de Vet, H.C.W.; Mouës, C.M.; Breugem, C.C.; van der Molen, A.B. Mink; Don Griot, J.P.W.
Objective: To develop a reliable and easy-to-use method to assess the nasolabial appearance of 18-year-old patients with unilateral cleft lip and palate (CLP). Design: Retrospective analysis of nasolabial aesthetics using a 5-point ordinal scale and newly developed photographic reference scale: the Cleft Aesthetic Rating Scale (CARS). Three cleft surgeons and 20 medical students scored the nasolabial appearance on standardized frontal photographs. Setting: VU University Medical Center, Amsterdam. Patients: Inclusion criteria: 18-year-old patients, unilateral cleft lip and palate, available photograph of the frontal view. Exclusion criteria: history of facial trauma, congenital syndromes affecting facial appearance. Eighty photographs were available for scoring. Main Outcome Measures: The interobserver and intraobserver reliability of the CARS for 18-year-old patients when used by cleft surgeons and medical students. Results: The interobserver reliability for the nose and lip together was 0.64 for the cleft surgeons and 0.61 for the medical students. There was an intraobserver reliability of 0.75 and 0.78 from the surgeons and students, respectively, on the nose and lip together. No significant difference was found between the cleft surgeons and medical students in the way they scored the nose ( P = 0.22) and lip ( P = 0.72). Conclusions: The Cleft Aesthetic Rating Scale for 18-year-old patients has a substantial overall estimated reliability when the average score is taken from three or more cleft surgeons or medical students assessing the nasolabial aesthetics of CLP patients.